Seasons 1 2 3 - Whitehouse, Patricia, 1958- (Chicago : Heinemann Library, 2003)
A counting book that features items associated with particular seasons, such as newborn lambs in the spring or sunglasses in the summer.
Includes index.
Booklist.
Horn Book.
2.9.
2.9
K-3
Keywords: Counting -- Juvenile literature; Seasons -- Juvenile literature; Counting; Seasons; Counting; Seasons